DAMPs and alarmin gene expression patterns in aging healthy and diseased mucosal tissues - Gonzalez, O. A.; Kirakodu, S. S.; Ebersole, J. L. (Frontiers in Oral Health, 2023)
Introduction Periodontitis is delineated by a dysbiotic microbiome at sites of lesions accompanied by a dysregulated persistent inflammatory response that undermines the integrity of the periodontium. The interplay of the altered microbial ecology and warning signals from host cells would be a critical feature for maintaining or re-establishing homeostasis in these tissues. Methods This study used a nonhuman primate model (Macaca mulatta) with naturally-occurring periodontitis (n = 34) and experimental ligature-induced periodontitis (n = 36) to describe the features of gene expression for an array of damage-associate molecular patterns (DAMPs) or alarmins within the gingival tissues. The animals were age stratified into: ≤3 years (Young), 7–12 years (Adolescent), 12–15 years (Adult) and 17–23 years (Aged). Gingival tissue biopsies were examined via microarray. The analysis focused on 51 genes representative of the DAMPs/alarmins family of host cell warning factors and 18 genes associated with tissue destructive processed in the gingival tissues. Bacterial plaque samples were collected by curette sampling and 16S rRNA gene sequences used to describe the oral microbiome. Results A subset of DAMPs/alarmins were expressed in healthy and naturally-occurring periodontitis tissues in the animals and suggested local effects on gingival tissues leading to altered levels of DAMPs/alarmins related to age and disease. Significant differences from adult healthy levels were most frequently observed in the young and adolescent animals with few representatives in this gene array altered in the healthy aged gingival tissues. Of the 51 target genes, only approximately ⅓ were altered by ≥1.5-fold in any of the age groups of animals during disease, with those increases observed during disease initiation. Distinctive positive and negative correlations were noted with the DAMP/alarmin gene levels and comparative expression changes of tissue destructive molecules during disease across the age groups. Finally, specific correlations of DAMP/alarmin genes and relative abundance of particular microbes were observed in health and resolution samples in younger animals, while increased correlations during disease in the older groups were noted. Conclusions Thus, using this human-like preclinical model of induced periodontitis, we demonstrated the dynamics of the activation of the DAMP/alarmin warning system in the gingival tissues that showed some specific differences based on age.